Optimization, Probiotic Characteristics, and Rheological Properties of Exopolysaccharides from Lactiplantibacillus plantarum MC5 - Xuefang Zhao; Qi Liang (Molecules, 2023)
This study optimized the exopolysaccharides (EPS) production for Lactiplantibacillus plantarum MC5 (Lp. plantarum MC5) and evaluated the resistance to human simulated digestive juices, antioxidant activity in vitro, and rheological properties of EPS-MC5. The results showed that maximum EPS production of 345.98 mg/L (about 1.5-old greater than the initial production) was obtained at optimal conditions of inoculum size (4.0%), incubation time (30 h), incubation temperature (34.0 °C), and initial pH value (6.40). Furthermore, the resisting-digestion capacity of EPS-MC5 after 180 min in α-amylase, simulated gastric juice (pH 2.0, 3.0, 4.0), and simulated intestinal juice (pH 6.8) was 98.59%, 98.62%, 98.78%, 98.86%, and 98.74%, respectively. In addition, the radical scavenging rates of DPPH•, ABTS•, •OH, and ferric-iron reducing power (OD700) of EPS-MC5 were 73.33%, 87.74%, 46.07%, and 1.20, respectively. Furthermore, rheological results showed that the EPS-MC5 had a higher apparent viscosity (3.01 Pa) and shear stress (41.78 Pa), and the viscoelastic modulus (84.02 and 161.02 Pa at the shear frequency of 100 Hz). These results provide a new insight into the application of EPS in human health and functional foods, which could also improve theoretical guidance for the industrial application of EPS.